Lima is good enough: exploring role of city in coping strategies and future planning among Venezuelan forced migrants in Peru - Karolina Sobczak-Szelc; Marcin Stonawski; Katarzyna Górska; Agnieszka Olter-Castillo; Jan Brzozowski; Silvana Gomez (Comparative Migration Studies)
Abstract The economic, political and social situation in Venezuela has forced millions of its citizens to leave their country (Mazuera-Arias et al., Sociodemographic Profiles and the Causesof Regular Venezuelan Emigration. International Migration, https://doi.org/10.1111/IMIG.12693 (2020)). Over the past eight years, we have witnessed an unprecedented exodus of this nature. In June 2024, there were 7.7 million Venezuelan migrants and refugees worldwide, of which 1.5 million have settled in Peru. Lima, the city hosting the majority of Venezuelans in Peru (R4V 2022), seems to be the final destination on their migration trajectory. Despite challenges and barriers related to the complex legal status landscape, the city fulfils aspirations and needs that drove Venezuelans to leave their country. Most importantly, Lima allows them to fulfil economic needs that are sufficient to survive and support those left behind. The objective of this paper is to demonstrate the principal challenges confronted by forced migrants from Venezuela on the labor market of Lima (Peru), the adaptation and coping strategies they employ to overcome them and how this situation influences their decisions on further (im)mobility. The results are based on a mixed-method approach with the use of quantitative and qualitative research methods. The quantitative methods employed include questionnaire interviews with Venezuelans in Lima and their Peruvian neighbors, while the qualitative methods comprise in-depth interviews with Venezuelans in Lima, their Peruvian neighbors, and experts in Peru, as well as observation during study visits to the research area.